A Subtitling Analysis Of Phrasal Verb In The Help Movie By Tate Taylor - Zulifa, Fitria Ulfa; , Drs. Dwi Harjanti. M. Hum; , Drs. Sigit Haryanto, M.Hum (2013)
The objectives of this research are to analyze the translation shifts of phrasal verb in The Help movie subtitle by Tate Taylor and to describe the equivalence of phrasal verb in The Help movie subtitle by Tate Taylor. This research belongs to a descriptive qualitative research. The data of the research are in form of clauses and sentences containing phrasal verb which have translation shift and translation equivalence in movie subtitle entitled The Help. The method of collection data is documentation method and technique for analyzing data is comparison method by comparing phrasal verb between source language and target language which is found in The Help movie subtitle. Having the analyzed the data, the researcher finds two findings of translating, they are translation shift and translation equivalence. In translation shift, the researcher applies Catford's theory and finds two types of translation shift, namely: level shift (2.90% phrasal verb are translated into noun, 47.67% into verb, 2.32% into adverb, 4.65% into adjective, 0.58% into clause, 21.51% into sentences) and category shift (1.74% phrasal verb are translated into adverb phrase, 1.16% into noun phrase, 13.95% into verb phrase, and 3.4% are not translated). In translation equivalence, the researcher applies Nida's theory. Besides, there are two types of translation equivalence, namely: dynamic equivalence 69.40% and formal equivalence 58.13% and 1.74 non equivalence.